Pathophysiology of atherosclerosis: the role of inflammation. - Tousoulis, D; Kampoli, A; Papageorgiou, N; Androulakis, E; Antoniades, C; Toutouzas, K; Stefanadis, C (2011)
Atherosclerosis is a disease of arteries and is characterized by endothelial dysfunction, vascular inflammation, and the build-up of lipids, cholesterol, calcium, and cellular debris within the intima of the vessel wall. A number of factors commonly characterized as "risk factors" for atherosclerosis have been identified to facilitate the development of atherosclerosis by decreasing NO bioavailability in the vascular endothelium. The serious clinical manifestations of atherosclerosis (including coronary heart disease, stroke, and peripheral vascular disease) augment the need of performing the appropriate diagnostic methods to the patients. The most important diagnostic methods include the usage of biochemical markers and the invasive and non-invasive imaging techniques assessing endothelial function. The main drug categories that have been proved to ameliorate the inflammatory state in atherosclerosis are angiotensin converting enzyme inhibitors/angiotensin receptors blockers, statins, and antioxidants.